2018
DOI: 10.1016/j.brs.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

TMS of primary motor cortex with a biphasic pulse activates two independent sets of excitable neurones

Abstract: BackgroundBiphasic pulses produced by most commercially available TMS machines have a cosine waveform, which makes it difficult to study the interaction between the two phases of stimulation.ObjectiveWe used a controllable pulse TMS (cTMS) device delivering quasi-rectangular pulse outputs to investigate whether monophasic are more effective than biphasic pulses.MethodsTemporally symmetric (“biphasic”) or highly asymmetric (“monophasic”) charge-balanced biphasic stimuli were used to target the hand area of moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Hence, it is an implicit assumption that interhemispheric differences in corticospinal excitability, as suggested by electrophysiological studies 15 , majorly rely on structural-functional differences in homologous motor pathways. In accord with previous electrophysiological studies 16 , our results indicated that RMT values of the motor-non-dominant hemisphere were on average larger than those of the motor-dominant hemisphere; however, these differences did not reach statistical significance, possibly due to methodological aspects, such as the use of a biphasic rather than monophasic current waveform 32 . Given these structural-functional leftward asymmetries in right-handers, we addressed whether stronger µ-phase-dependency of corticospinal excitability could occur when stimulating the motor-dominant compared to the motor-non-dominant M1.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, it is an implicit assumption that interhemispheric differences in corticospinal excitability, as suggested by electrophysiological studies 15 , majorly rely on structural-functional differences in homologous motor pathways. In accord with previous electrophysiological studies 16 , our results indicated that RMT values of the motor-non-dominant hemisphere were on average larger than those of the motor-dominant hemisphere; however, these differences did not reach statistical significance, possibly due to methodological aspects, such as the use of a biphasic rather than monophasic current waveform 32 . Given these structural-functional leftward asymmetries in right-handers, we addressed whether stronger µ-phase-dependency of corticospinal excitability could occur when stimulating the motor-dominant compared to the motor-non-dominant M1.…”
Section: Discussionsupporting
confidence: 89%
“…The integrated model enabled analysis of waveform-and direction-dependent effects that would be indiscernible using the E-field distribution alone. TMS of the motor cortex produces motor evoked potentials (MEPs) with 2-3 ms longer latencies for current in the A-P than in the P-A direction 8,26,29,33,34 . In the model, reversing the current direction for the monophasic waveform from P-A to A-P produced an anterior shift in the spatial distribution of activation of L2/3 and L5 PCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the spatial distribution of the E-field alone cannot predict the physiological effects of stimulation, and TMS can recruit distinct neural populations or elements based on different temporal dynamics of the E-field waveform (e.g. pulse shape, direction, width, and phase amplitude asymmetry) [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the simultaneous activation of several muscles by TMS at one point is a result of several key factors: (1) the non-focality of TMS itself, where a spread of induced electric field leads to the activation of a considerable cortical area (Wassermann et al, 2008); (2) the primarily indirect TMS effect on the pyramidal neurons (Seo, Schaworonkow, Jun, & Triesch, 2016;Spampinato, 2020); (3) the co-location of the cortical neuronal populations, innervating different spinal motoneurons pools (Capaday et al, 2013;Schieber, 2001); and (4) cross-talk between the muscles at the peripheral level when using surface EMG (Selvanayagam et al, 2012). TMS focality depends on the coil configuration and on the intensity, shape and direction of the pulse (Koponen, Nieminen, Mutanen, Stenroos, & Ilmoniemi, 2017;Rossini et al, 2015;Sommer et al, 2006Sommer et al, , 2018Tugin et al, 2020). We utilized the figure-of-eight coil used for nTMS presurgical mapping (Krieg et al, 2017) and a biphasic pulse shape, allowing to use less intensity (Raffin et al, 2015).…”
Section: Methodological Considerations and Future Studiesmentioning
confidence: 99%
“…We used a biphasic pulse shape because it is the most common in TMS mapping studies with patients (Lüdemann-Podubecká & Nowak, 2016;Takahashi, Vajkoczy, & Picht, 2013). However, considering that a biphasic pulse may activate two distinct neuronal pools (Sommer et al, 2018); it may be informative to investigate how the reliability of the within-limb TMS somatotopy differs when using monophasic current configurations.…”
Section: Methodological Considerations and Future Studiesmentioning
confidence: 99%